Pendampingan Baca Tulis Al Qur’an Siswa SMP di Kawasan Terdampak ROB Pekalongan - Dian Dewi Lestari; Melanis Tofah; Haris Darmawan (Sekolah Pascasarjana Universitas Negeri Jakarta, 2024)
Siwalan's location in a coastal area affected by tidal floods affects children's enthusiasm for learning, especially in Islamic religious education. Seeing the condition of the area around SMP N 2 Siwalan, which is often affected by tidal floods, is one of the reasons why students lack knowledge about reading and writing the Koran. because when the tidal flood hits, students will not be able to go to the Koran at TPQ or Madrasahs that are affected by this tidal flood. This research is field research using a qualitative descriptive approach with data collection techniques of observation, interviews and documentation. In overcoming difficulties in learning the Qur'an, what has been done is by organizing a Qur'an Reading and Writing program.